Dietary intervention with salvia hispanica (Chia) oil improves vascular function in rabbits under hypercholesterolaemic conditions - Sierra, Liliana Beatríz (2015)
The effects of dietary supplementation with Salvia hispanica (chia) oil on vascular function in hypercholesterolaemic rabbit were examined. Rabbits were fed either regular diet (CD) or 10% chia oil in regular diet or 1% cholesterol diet (HD) or diet containing 1% cholesterol and 10% chia oil (HD-Ch) during 5?6 weeks. HD increased total cholesterol, LDL and triacylglycerol levels. HD-Ch significantly attenuated the triacylglycerol rise and increased alpha linolenic acid (ALA) levels. Aorta from hypercholesterolaemic rabbits exhibited an impaired relaxation response to acetylcholine (Ach), reduced NO-release and increased intima/media ratio. Including chia oil in the HD partially normalized the response to Ach and the intima/media ratio, and totally restored the NO-release. In addition, dietary supplementation with chia oil blunted the contractile response to angiotensin II and noradrenaline. These findings suggest that increased ALA levels induced by dietary chia oil could improve vascular function under hypercholesterolaemic conditions and therefore could serve as a true functional food.